Brightness Motivates Healthy Behaviors: The Role of Self-Accountability. Issue 2 (February 2022) - Chan, Eugene Y.
A growing literature suggests the possibility that brightness (vs. darkness) affects myriad human behaviors and how people think. One stream suggests that brightness increases self-awareness. We extend these findings and formally hypothesize that brightness (vs. darkness) increases self-accountability, thereby motivating people to take actions to meet their self-standards for health, of which most people generally fall short. Three experimental studies were conducted. The results indicate that brightness increases healthier food choices (Study 1) and physical activity intentions (Study 2). Self-accountability mediates the effect (Study 2), while manipulating self-accountability moderates it (Study 3), thereby providing evidence for its likely causal role in explaining the impact of brightness on facilitating healthy behaviors. The findings offer insights into the positive benefits of brightness beyond past findings that it improves mood and psychological well-being. Limitations of the current research as well as future research directions are discussed.